2002
DOI: 10.1002/ijc.10193
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between vascular endothelial growth factor‐C expression and invasion phenotype in cervical carcinomas

Abstract: The correlation between vascular endothelial growth factor (VEGF)-C gene expression and in vitro invasive activity and matrix metalloproteinase (MMP)-2 or 9 gene expression and proteolytic activity in 11 cervical carcinoma cell lines, was investigated. Immunohistochemical expression of VEGF-C in 52 cervical carcinoma tissues was also correlated with tumor aggressiveness with respect to clinicopathologic features, tumor vascularity, MMP-2 expression and patient outcome. Expression of VEGF-C mRNA differed remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 34 publications
5
52
0
2
Order By: Relevance
“…Evidence suggests a strong correlation between VEGF-C expression and lymph node metastasis formation (Yonemura et al, 1999). Most recent reports suggest that VEGF-C plays an extremely important role in invasion in breast (Mattila et al, 2002), cervical (Ueda et al, 2002), colon (Furudoi et al, 2002), and gastric cancer (Takahashi et al, 2002). In our study, VEGF-C was highly overexpressed in most of the mutants, and in fibrosarcoma HT1080, glioma T98G, and prostate cancer DU145 cells.…”
Section: Discussionsupporting
confidence: 64%
“…Evidence suggests a strong correlation between VEGF-C expression and lymph node metastasis formation (Yonemura et al, 1999). Most recent reports suggest that VEGF-C plays an extremely important role in invasion in breast (Mattila et al, 2002), cervical (Ueda et al, 2002), colon (Furudoi et al, 2002), and gastric cancer (Takahashi et al, 2002). In our study, VEGF-C was highly overexpressed in most of the mutants, and in fibrosarcoma HT1080, glioma T98G, and prostate cancer DU145 cells.…”
Section: Discussionsupporting
confidence: 64%
“…Overexpression of vascular endothelial growth factor C (VEGF-C) has been detected in numerous cancers (34)(35)(36)(37), and the role of VEGF-C in promoting lymphatic metastasis has been demonstrated in several VEGF-C overexpression animal models of mammary carcinoma (38)(39)(40). Previous study revealed that Six1 could coordinate with transforming …”
Section: Six1 Expression N -----------------------------------------mentioning
confidence: 99%
“…Overexpression of VEGF-C has been implicated in a number of cancers (35)(36)(37)(38), and its role in promoting lymphatic metastasis has been demonstrated in several VEGF-C overexpression animal models of mammary carcinoma (25)(26)(27). Although growth factors have been found to regulate the expression of VEGF-C (39,40), here, we demonstrate for what we believe to be the first time that SIX1 can directly upregulate VEGFC through transcription and stimulate VEGF-C-mediated lymphangiogenesis in breast cancer cells, thereby contributing to lymphatic dissemination and distant metastasis.…”
Section: Six1 Is Overexpressed In 50% Of Primary Tumors and In An Evenmentioning
confidence: 99%